First aid for the medicine clerkship - Kaufman, Matthew S. (McGraw-Hill Medical, 2010)
Section I: How to succeed in the medicine clerkship -- Section II: Database of high-yield facts -- Cardiology -- Endocrinology -- Hematology-oncology -- Infectious disease -- Nephrology and acid-base disorders -- Pulmonology -- Rheumatology -- Neurology -- Dermatology -- Health maintenance and evidence-based medicine -- Section III: Classified -- Index.